Circus therapy in pediatric neuropsychological rehabilitation: an experience report (Research, Society and Development, 2022)
This article reports the author’s experience with the use of circus therapy activities in online neuropsychological rehabilitation of children with learning difficulties. It describes the results of free observation of one session in the PANDA Project. Four children were present, who previously underwent the neuropsychological assessment (NA) process and belong to a recurrent neuropsychological rehabilitation group. Three activities were performed in the meeting: the exhibition of a short film with paper dolls, "A Dor Azul" (The Blue Pain) (Cia dos Afetos, 2020); juggling with grocery bags; and look, feel, act (Trupe Trapia, 2021) an introductory exercise to clowning. According to the author's perception, three of the four children were more committed and motivated to participate in the proposed activities compared to the previous rehabilitation sessions, especially juggling with grocery bags. The fourth child, diagnosed with Childhood Autism (World Health Organization 1992), was resistant to most activities - except the last one, in which he was able to select an object of his interest. Based on the authors' experience, a bank of activities is being created for the permanent use of circus practices by the neuropsychological rehabilitation groups of the PANDA project.